Experimental and numerical failure analysis of notched quasi-unidirectional laminates at room temperature and elevated temperature. (15th January 2017) - Flore, D.; Stampfer, B.; Wegener, K.
Abstract: In this work an approach to predict the strength of notched structures made of quasi unidirectional glass fibre epoxy is presented. It takes into account the fabric specific behaviour in terms of hardening and softening. Four macroscopic ply failure modes are considered according to the Hashin criterion, depending on the direction of loading. Material hardening and softening is implemented according to Continuum Damage Mechanics. The hardening mechanism is modelled separately for matrix tension and shear. The softening mechanism is modelled by the incorporation of fracture toughness according to the failure mode (fibre/matrix failure in tension/compression). A new technique is proposed to determine the fracture toughness from uniaxial tension/compression tests of unidirectional notched laminate specimens. Special interest is given to the temperature impact on the material properties (elastic parameters, strengths and fracture energy) in a wide range (−40 °C to 160 °C). Since the interval covers the rubber temperature of epoxy the approach's reliability under such conditions is examined as well.